ECO-ENZYME BASED ON HORTICULTURAL WASTE'S WITH VARYING CONCENTRATION ON THE ACTIVITY OF CANDIDA ALBICANS FUNGUS IN VITRO - Najla Lubis; Ruth Riah Ate Tarigan; Dwi Hayati (RADJA PUBLIKA, 2025)
This study aims to evaluate the potential of eco-enzyme (EE) derived from horticultural waste as an antifungal agent against Candida albicans, a major pathogen responsible for infections in both humans and plants. Eco-enzyme is a product of fermentation that involves using organic waste, such as fruit and vegetable peels, which are often discarded and contribute to environmental pollution. In this research, eco-enzyme was prepared using a variety of horticultural waste, including pineapple, orange, papaya, and mango peels. The eco-enzyme was then tested at various concentrations (1:0, 1:10, 1:50, and 1:100) to assess its antifungal activity against Candida albicans using the in-vitro disk diffusion method. The results indicated that eco-enzyme, particularly at the 1:50 dilution, demonstrated significant antifungal activity, with a clear inhibition zone observed around the disc. The presence of bioactive compounds such as flavonoids, tannins, and saponins in the eco-enzyme is believed to be responsible for its ability to inhibit fungal growth by disrupting the cell membrane structure and metabolic functions of the pathogen. These findings suggest that eco-enzyme can serve as an effective natural alternative to conventional chemical antifungal agents, offering a more sustainable and eco-friendly solution for managing fungal infections. Furthermore, this study emphasizes the importance of utilizing agricultural waste for eco-enzyme production, providing an innovative way to address the global challenge of organic waste disposal while promoting sustainable agricultural practices. The research contributes to the growing body of knowledge on the benefits of eco-enzyme in both agricultural and public health applications, offering promising possibilities for its wider use in fungal disease management